Shape of the equatorial magnetopause affected by the radial interplanetary magnetic field. (15th November 2017) - Grygorov, K.; Šafránková, J.; Němeček, Z.; Pi, G.; Přech, L.; Urbář, J.
Abstract: The ability of a prediction of the magnetopause location under various upstream conditions can be considered as a test of our understanding of the solar wind-magnetosphere interaction. The present magnetopause models are parametrized with the solar wind dynamic pressure and usually with the north-south interplanetary magnetic field (IMF) component. However, several studies pointed out an importance of the radial IMF component, but results of these studies are controversial up to now. The present study compares magnetopause observations by five THEMIS spacecraft during long lasting intervals of the radial IMF with two empirical magnetopause models. A comparison reveals that the magnetopause location is highly variable and that the average difference between the observed and predicted positions is ≈ + 0.7 R E under this condition. The difference does not depend on the local times and other parameters, like the upstream pressure, IMF north-south component, or tilt angle of the Earth dipole. We conclude that our results strongly support the suggestion on a global expansion of the equatorial magnetopause during intervals of the radial IMF. Highlights: Analysis of prolonged intervals of radial IMF. Comparison of magnetopause locations with model predictions under this condition. Estimation of average magnetopause difference (+0.7 Re). Global expansion without dependence on local time and other parameters.